Treatment of Behcet’s disease - Fereydoun Davatchi; Nasrin Moghimi; Mohammad Mousavi; Alimohammad Fatemi (Chronic Diseases Journal, 2013)
Behcet’s disease is a systemic disease classified among vasculitides. Major manifestations are mucous membrane lesions (oral aphthosis and genital aphthosis), skin manifestations (pseudofolliculitis, erythema nodosum), ocular manifestations (uveitis, retinal vasculitis), joint manifestations, vascular lesions (small to large vessel thrombosis, aneurysm), gastrointestinal manifestations, orchiepididymitis, and some rare manifestations like cardiac, pulmonary, and renal impairment. Diagnosis is mainly clinical. The International Diagnosis Criteria for Behcet’s Disease may be of help. The gold standard of treatment for mucocutaneous lesions is colchicine. In refractory cases, levamisole, thalidomide, and dapsone may be of help. For major organ involvement like the eyes and the brain, immunosuppressive drugs and prednisolone are the gold standard. In refractory cases, biological agents are the last resort. For gastrointestinal manifestations, sulfasalazine and prednisolone are the first-line treatment. For vascular involvement, the first line treatment was anticoagulation, but recently it was shown that immunosuppressive drugs and prednisolone were confirmed to be the best. In all refractory cases and for all different organs, the last resort is biological agents.